DOI: 10.18174/546382
|View full text |Cite
|
Sign up to set email alerts
|

The multifunctional role of marine sponges in multi-trophic mariculture systems : towards sustainable use of sponges in polluted marine waters

Abstract: This research was conducted under the auspices of the Graduate School for Wageningen Institute of Animal Sciences (WIAS)In the chambered cavities of sponges pinna-guards or parasites are found. And over the chambers there is a kind of spider's web, by the opening and closing of which they catch mute fishes; that is to say, they open the web to let the fish get in, and close it again to entrap them.Of sponges there are three species; the first is of loose porous texture, the second is close textured, the third,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Earlier research employed feeding trends of organisms and proper methods to assess the efficacy of pure chemicals or crude extracts from sponges as predatordefense mechanisms, mostly in the temperate and tropical Caribbean, Mediterranean, Pacific, and Southwestern Atlantic (McGrath et al, 2018;Gökalp, 2021;Maslin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier research employed feeding trends of organisms and proper methods to assess the efficacy of pure chemicals or crude extracts from sponges as predatordefense mechanisms, mostly in the temperate and tropical Caribbean, Mediterranean, Pacific, and Southwestern Atlantic (McGrath et al, 2018;Gökalp, 2021;Maslin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…According to our hypothesis, chemical cues may attract O. savignyi to G. corticostylifera, which may also prevent epibionts and predators (Pochon et al, 2001;Gökalp, 2021). The focus of this research has been to assess the functional relevance of G. corticostylifera secondary metabolites as antifoulant against mussels, protection against generalist fish, and chemical cues to affiliated brittle stars.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the authors concluded that, due to evident bacterial accumulation by the sponge, the co-occurrence of Hymeniacidon perlevis with M. galloprovincialis was a powerful tool to reduce bacterial loads in shellfish farming areas, thus playing a role in mitigating health risks associated with the consumption of edible mussels (Longo et al, 2016). Sponges act as biofilters accumulating toxic substances up to higher levels of the food chain (Fasulo et al, 2015;Gokalp, 2021). In particular, they can absorb pollutants especially through food (Carmen Casado-Martinez et al, 2010), suggesting a potential role of these organisms in bioremediation processes.…”
Section: Bioremediation By Spongesmentioning
confidence: 99%
“…Besides the above, sponges have further been identified as potential bioremediator of organic waste, such as that which is produced by commercial aquaculture farms due to their extraordinary filtering capacities [28,29]. There has been an increasing interest over the past decade in this field with multiple studies indicating the positive effects of sponge-integrated aquaculture systems [21,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%